Pengaruh Fanatisme Korean Pop Terhadap Perilaku Imitasi Remaja - Dea Aulia; Miftahuddin Miftahuddin; Istiqomah Istiqomah; Muhammad Fahli Zatrahadi; Darmawati Darmawati (Fakultas Tarbiyah dan Keguruan, 2022)
This research is motivated by one of the tasks of adolescent development, namely to find a model human who becomes their identity, the model human who becomes the identity of teenagers in this study is a k-pop idol, besides that at the psychosocial stage of adolescence, they are in the stage of identity search versus identity confusion, which from this stage, many teenagers fail in a process of forming self-identity which will cause teenagers to have fanaticism, this fanaticism arises as a result of the process of cultural interaction between individuals with one another, so that it will give birth to a new form of behavior, namely imitation behavior. The problem in this study is whether there is a significant influence between k-pop fanaticism on the behavior of teenagers in the purple army community in Pekanbaru. While the purpose of the study was to see if there was a significant influence between k-pop fanaticism on adolescent behavior. In obtaining the data in the study, the author uses quantitative research methods with a population of 57 people with data collection techniques using questionnaires and analyzed through simple linear regression.